A trait emotional intelligence perspective on schema modes. Issue 2 (28th August 2020) - Jacobs, Ingo; Wollny, Anna; Seidler, Juliana; Wochatz, Germar
Abstract : Schema modes (or modes ) are a key concept in the theory underlying schema therapy. Modes have rarely been related to established models of personality traits. The present study thus investigates the associations between trait emotional intelligence ( TEI ) and 14 modes, and tests a global TEI–mode factors–general psychological distress mediation model. The study draws on self‐report data from 173 inpatients from a German clinic for psychosomatic medicine. Global TEI correlated positively with both healthy modes (happy child and healthy adult) and negatively with 10 maladaptive modes. When modes were regressed on the four TEI factors, six (emotionality), five (well‐being), four (sociability), and four (self‐control) significant partial effects on 10 modes emerged. In the parallel mediation model, the mode factors internalization and compulsivity fully mediated the global TEI–general psychological distress link. Implications of the results for the integration of modes with traits in general and with TEI in particular as well as implications of low TEI as a transdiagnostic feature of personality malfunctioning are discussed.